Multiple endocrine neoplasia type 2 – solving the puzzle - Ajay K. Jha; Ashok Sunder; Sridhar Pradhan (Journal of Family Medicine and Primary Care)
Multiple endocrine neoplasia (MEN) are tumors that involve two or more endocrine glands. It can also involve other organs and tissues as well. Out of the four types of MEN type 2 is the most common. In MEN type 2 or type 3, paraganglioma is rare, but in our case, medullary thyroid carcinoma (MTC), hyperparathyroidism, and pheochromocytoma were associated with the paraganglioma.